English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1) Simplify by combining like terms:
sqrt27 - sqrt3 + 2sqrt12

2) Solve:
[sqrt(3x - 2)] + 2 = 5

2006-11-27 13:41:13 · 3 answers · asked by GMEN 1 in Science & Mathematics Mathematics

3 answers

For the first one, 27 = 3^2*3, so sqrt(27) can be written as 3sqrt(3). So sqrt(27) - sqrt(3) is 2sqrt(3). Similarly, 12 = 2^2*3, so sqrt(12) is 2sqrt(3). 2sqrt(3) + 2sqrt(3) = 4sqrt(3).

For the second one, start by subtracting 2 from each side. You get sqrt(3x-2) = 3. Then square both sides. That gives 3x-2 = 9. Add 2 to each side: 3x = 11. Divide by 3: x = 11/3 = 3 2/3.

2006-11-27 13:46:03 · answer #1 · answered by Amy F 5 · 0 0

#1) √27 - √3 + 2√12
√9√3 - √3 + 2* √4*√3
3√3 - 1√3 + 2*2√3
3√3 - 1√3 + 4√3
(3-1+4)√3
6√3

#2) √(3x-2) + 2 = 5, subtract 2 from both sides
√(3x-2) = 5 -2
√(3x-2) = 3, square both sides
3x-2 = 9, add 2 to both sides
3x = 9 + 2
3x = 11, divide both sides by 3
x = 11/3, or 3 2/3

2006-11-27 13:57:04 · answer #2 · answered by MrDanaH 2 · 0 0

did you even try to answer this question??? If you did then you could have seen that it was easier than it seemed.

2006-11-27 13:50:24 · answer #3 · answered by lavender tots 4 · 0 0

fedest.com, questions and answers